2019
DOI: 10.1186/s13578-019-0338-3
|View full text |Cite
|
Sign up to set email alerts
|

X-linked inhibitor of apoptosis protein accelerates migration by inducing epithelial–mesenchymal transition through TGF-β signaling pathway in esophageal cancer cells

Abstract: Background The prognosis of esophageal cancer is still dismal because of its high probability of metastasis that is likely related to the cellular process of epithelial–mesenchymal transition (EMT). Recent studies have shown a novel role of X-linked inhibitor of apoptosis protein (XIAP) in regulating the migration process of cancer cells and, therefore, linking to progression and poor prognosis of cancer. Methods The expression of XI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…Tumor cells that undergo the EMT lose cell–cell adhesion and polarity and acquire mesenchymal characteristics with stronger migration and invasion properties 26 . Accumulating recent evidence indicated that the EMT is common in tumor cells during tumor progression and correlates with local invasiveness and metastatic potential of various tumors, including ESCC 15,17,27‐29 . Morphological changes caused by BACH1 were observed in the present study; BACH1 overexpression increased the expression of N‐cadherin, vimentin, and Slug and decreased the level of the epithelial marker E‐cadherin, and knockdown of BACH1 showed the opposite effects.…”
Section: Discussionsupporting
confidence: 65%
“…Tumor cells that undergo the EMT lose cell–cell adhesion and polarity and acquire mesenchymal characteristics with stronger migration and invasion properties 26 . Accumulating recent evidence indicated that the EMT is common in tumor cells during tumor progression and correlates with local invasiveness and metastatic potential of various tumors, including ESCC 15,17,27‐29 . Morphological changes caused by BACH1 were observed in the present study; BACH1 overexpression increased the expression of N‐cadherin, vimentin, and Slug and decreased the level of the epithelial marker E‐cadherin, and knockdown of BACH1 showed the opposite effects.…”
Section: Discussionsupporting
confidence: 65%
“…XIAP has been reported to act as a cofactor in TGFβ signaling independent of its role in apoptosis by associating with members of the type I class of TGFβ receptors (Birkey Reffey, Wurthner, Parks, Roberts, & Duckett, 2001). Also, in esophageal carcinoma cell lines, XIAP has been reported to enhance cell migration by activating TGFβ, which then promotes EMT (Jin, Lu, Wang, Zhao, & Xue, 2019). As discussed previously, IAPs are now well-known regulators of the canonical and non-canonical NFB signaling, which is also known to play an important role in cancer cell migration/invasion by regulating Snail and other EMT regulators (Y.…”
Section: Role Of Iaps In Regulating Cell Adhesion Moleculesmentioning
confidence: 93%
“…Several studies have devoted to investigate the role of TGF-β signaling pathway in ESCC. The majority demonstrated the tumor-promoting role of TGF-β signaling pathway in ESCC [ 32 34 ], while several studies draw the contrary conclusion [ 35 , 36 ]. We discovered TGF-β signaling pathway listed on the top one of the pathways associated with ATAD2 via RNA-sequencing and proved the regulation role of ATAD2 on TGF-β1, which clarified a tumor-promoting role of TGF-β signaling pathway in ESCC.…”
Section: Discussionmentioning
confidence: 99%